Peter R. Odell, Oil and World Power. Background to the Oil Crisis. Penguin Books; 1ª edición 1970, 3ª edición 1974. Pelican Geography and Enviroammental Studies. - Siebert, Jack Gerardi (Estudios de Asia y África, 1976)
-